دور المعرفة الفكرية في تنمية المستدامة لقطاع التأمين في العراق: (بحث تطبيقي في عينة من شركات التامين العراقية - الخاصة) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims at identifying the relationship between the process of managing intellectual knowledge and its impact on the development and sustainability of the Iraqi insurance sector by conducting an analysis of the types of intellectual knowledge owned by Iraqi insurance companies and the amount of revenues generated from each type of services provided to customers.                                                                                       In order to achieve this objective, the research sample was selected from a sample of Iraqi insurance companies listed in the Iraqi Stock Exchange (Al-Ameen Insurance Company, Al Ahlia Insurance, Al-Hamra Insurance, Gulf Insurance, Dar Al-Salam Insurance) and relying on published financial reports for the five fiscal years (2013-2017), and by testing the hypothesis of research on the sample to achieve the goal of the research.   The main conclusion of the research is that there is a great role for intellectual knowledge in the process of diversification of insurance services provided by Iraqi companies to customers in a way that reflects on increasing financial returns, which in turn leads to the development and sustainability of the insurance sector in Iraq   The most important thing recommended by the research is the need to interest Iraqi insurance companies with the intellectual knowledge that they have and develop in a manner that achieves the development of the insurance sector and increases the financial returns achieved.